Kontribusi Pondok Pesantren dalam Mengembangkan Kemandirian dan Kreativitas Santri - Lia Paryanti, Eka; Irhamudin, Irhamudin; Wijaya, Adi (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2024)
This research discusses the role of the Hidayatul Qur’an Islamic Boarding School in shaping the independence and creativity of its students in Sumbersari, East Lampung. The Islamic boarding school plays an important role in forming the independence and creativity of the Hidayatul Qur’an students. The purpose of this research is to understand the role of the Islamic boarding school in shaping the independence and creativity of the students. This research uses a qualitative approach with a field research method, and data collection was carried out through interviews, observations, and documentation. Based on the results of the observation and interviews conducted by the researcher at the Hidayatul Qur’an Islamic Boarding School with the management, several factors hindering the development of independence and creativity among the students were identified. These factors include habits and personalities that have not yet adapted to the conditions at the boarding school, a lack of awareness regarding personal needs in various aspects, and continued dependency on their parents